Maintaining and creating value through preservative post-acquisition practices : The perspective of an acquired company - Haapaniemi, Kati (My University, 2025)
Research in Strategic Management has shown that acquisitions are a demanding means of growth, and the benefits they bring can be contradictory. Acquisitions have been studied from various perspectives, with the process perspective being the closest to this research. This study focuses on the phase of an acquisition in which the actual purchase agreement has been made, and the aim is to concentrate on maximizing the value enabled by the acquisition. The objective of the research is to investigate what kinds of value-preserving and value-creating practices are maintained and developed in situations where the acquired company remains an independent entity and is not merged into the parent company. The theoretical framework of the study draws on previous findings from three areas of strategic management research. Firstly, it considers results from earlier integration research, which suggest that the success of the integration phase is influenced by factors such as the contextual elements of the acquisition, strategic/structural management actions during integration, human-oriented leadership practices, and the interactions between different groups at the organizational level. It also acknowledges that so-called preservation acquisitions have their own distinct value creation processes. Secondly, the framework examines integration from the perspective of the strategy-as-practice research field, in which strategy is seen as a set of social practices. These practices act as a bridge between the micro level (individual actors) and the macro level (broader social structures related to strategy). Previous strategy-as-practice research has not always sufficiently addressed the process through which broader social structures and the more limited scope of individual agency intersect. This study aims to explore how the micro and macro levels meet in the value-preserving and value-creating practices of an acquired company in preservation acquisitions. Thirdly, the framework utilizes strong structuration theory, which builds upon the original structuration theory but better incorporates the empirical research perspective and the interaction between the micro and macro levels of social reality. The data consists of semi-structured interviews with key individuals from the acquired company. The results indicate that practices aimed at preserving and creating value are crucial to the success of the acquired company. The management of the acquired company, together with representatives from the parent company, strives to maintain the independent position and capabilities of the daughter. In this acquisition, the physical resources of the daughter company, such as production technology, also played an important role in preserving value. New value can be created through both strategic and operational forms of collaboration. The interviewees also had ideas for cooperative forms that had not yet been implemented. Among the management actions directed at the organizational level, emphasis was placed not only on the independent position of the daughter but also on reassuring communication to staff about the continuity of the acquired company, which can also be seen as an effort to preserve capabilities. The results are in many ways aligned with previous integration research, and the characteristics of preservation acquisitions are strongly present. Further research is needed, particularly on the specific features of preservation acquisitions and their links to acquisition success, as well as on the broader application of strong structuration theory in strategy-as-practice research beyond the context of integrations.

Strategisen johtamisen tutkimus on osoittanut, että yritysostot ovat vaativa kasvun keino, jonka tuomat hyödyt voivat olla ristiriitaisia. Yritysostoja on tutkittu useista näkökulmista, joista prosessinäkökulma on lähimpänä tätä tutkimusta. Tämä tutkimus keskittyy yritysoston siihen vaiheeseen, jossa varsinainen ostosopimus on tehty ja tavoitteena on keskittyä yritysoston mahdollistaman arvon maksimoimiseen. Tutkimuksen tavoitteena on selvittää, millaisia tytäryhtiön arvoa suojaavia ja arvoa luovia käytänteitä pyritään säilyttämään ja muodostamaan tilanteessa, jossa tytäryhtiö jää yritysoston jälkeen itsenäiseksi yritykseksi eli sitä ei sulauteta emoyhtiöön. Tutkimuksen viitekehys hyödyntää aikaisempia tuloksia kolmelta strategisen johtamisen tutkimusalalta. Ensinnäkin huomioidaan aikaisemman integraatiotutkimuksen tuloksia, joiden mukaan integraatiovaiheen onnistumiseen vaikuttavat muun muassa yritysoston kontekstuaaliset tekijät, integraatiovaiheen strategiset/rakenteelliset johtamistoimenpiteet, integraatiovaiheen pehmeän johtamisen eli ihmisjohtamisen toimenpiteet sekä organisaatiotasolla tapahtuvat eri ryhmien väliset vuorovaikutukset. Lisäksi huomioidaan se, että ns. säilyttävällä yritysostolla on täysin omanlaisensa arvonmuodostamisen prosessi. Toiseksi, viitekehyksessä integraatiota tarkastellaan strategia käytänteinä -tutkimusalan näkökulmasta, jossa strategia nähdään sosiaalisina käytänteinä. Käytänteet toimivat siltana mikrotason eli yksittäisten toimijoiden sekä makrotason eli strategioihin liittyvien laajempien sosiaalisten rakenteiden välillä. Aikaisempi strategia käytänteinä -tutkimus ei ole aina tarpeeksi huomioinut prosessia, jossa laajempi sosiaalisten rakenteiden taso ja suppeampi yksilön toimijuuden taso kohtaavat. Tämä tutkimus pyrkii selvittämään, miten yksilötaso ja makrotaso kohtaavat säilyttävän yritysoston arvoa säilyttävissä ja luovissa tytäryhtiön käytänteissä. Kolmanneksi, viitekehys hyödyntää vahvaa strukturaatioteoriaa, joka ottaa alkuperäistä strukturaatioteoriaa paremmin huomioon empiirisen tutkimuksen näkökulman ja sosiaalisen todellisuuden mikro- ja makrotasojen vuorovaikutuksen. Aineistona ovat puolistrukturoidut haastattelut tytäryhtiön avainhenkilöiden kanssa. Tulokset osoittavat, että arvon säilyttämisen ja luomisen käytänteet ovat tärkeitä tytäryhtiön menestymisen kannalta. Tytäryhtiön johto pyrkii yhdessä emoyhtiön edustajien kanssa säilyttämään tyttären itsenäisen aseman sekä tytäryhtiön kyvykkyydet. Tässä yritysostossa myös tytäryhtiön fyysisillä resursseilla, kuten tuotantoteknologialla, oli tärkeä rooli arvon säilyttämisessä. Uutta arvoa voidaan luoda sekä strategisten että operationaalisten yhteistyömuotojen kautta. Haastateltavilla oli myös ideoita yhteistyömuotoihin, joita ei toistaiseksi ollut toteutettu. Organisaatiotasolle suunnatuissa johtamistoimenpiteissä korostuivat paitsi tytäryhtiön itsenäinen asema myös henkilöstölle suunnattu rauhoittava viestintä tytäryhtiön jatkuvuudesta, jonka voidaan myös katsoa pyrkivän kyvykkyyksien säilyttämiseen. Tulokset ovat monissa kohdin linjassa aikaisemman integraatiotutkimuksen kanssa, ja muun muassa säilyttävän yritysoston piirteet ovat vahvasti läsnä. Lisätutkimusta tarvitaan erityisesti säilyttävien yritysostojen erityispiirteistä ja niiden yhteyksistä yritysostojen onnistumiseen sekä vahvan strukturaatioteorian hyödyntämisestä strategia käytänteinä -tutkimuksessa laajemminkin kuin integraatioiden yhteydessä.
Keywords: yrityskaupat; arvonluonti; rakenteistumisteoria; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development